2010
DOI: 10.1002/jcla.20397
|View full text |Cite
|
Sign up to set email alerts
|

Role of tissue disorder markers in the evaluation of disease progress and outcome prediction: a prospective cohort study in non‐cardiac critically ill patients

Abstract: All the six tissue disorder markers are predictors of disease severity, organ failure, and outcome in non-cardiac critically illness. Among them, Mb plays a pivotable role. The combined use of Mb and APACHE-II suggest an effective method to determine the outcome of critical ill syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…In this four-year retrospective study, 56.5% of the critically ill patients showed increased myoglobin levels (≥150 μg/mL). Our results were similar to those of a previous study with 179 critically ill patients, which reported that 40.8% of the critically ill patients without ACS had elevated myoglobin level and 18 (10%) patients presented severe myoglobin elevation (≥1,000 μg/mL) on admission to the ICU ( 5 ). The previous study included critically ill patients without surgery, while in our study, two-thirds were postsurgical patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this four-year retrospective study, 56.5% of the critically ill patients showed increased myoglobin levels (≥150 μg/mL). Our results were similar to those of a previous study with 179 critically ill patients, which reported that 40.8% of the critically ill patients without ACS had elevated myoglobin level and 18 (10%) patients presented severe myoglobin elevation (≥1,000 μg/mL) on admission to the ICU ( 5 ). The previous study included critically ill patients without surgery, while in our study, two-thirds were postsurgical patients.…”
Section: Discussionsupporting
confidence: 91%
“…Since recently, myoglobin has been used in the prognostic assessment of critically ill and postoperative patients (3,4). A prospective study of critically ill patients without cardiac disease showed that elevated myoglobin level within 24 h of admission was a major risk factor for in-hospital death and 180-day death (5). In addition, myoglobin can be used to predict mortality and conversion to critical illness in severe and critically ill COVID-19 patients, with better efficacy than troponin (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…AST had a prediction role in the severity of disease and U.S grade. However, it has not been a reliable finding, because AST level changed in many conditions such as systemic disorder ( Tables 2 and 3 ) ( 28 , 30 ). Nevertheless, in several papers like Purnak T, Sogabe M and Lin YC, AST was a predictor of NAFLD severity and U.S significantly ( 26 , 27 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…AST is an intracellular enzyme that is released into serum when cell death occurrs. It is not a specific marker for liver cell death and may be elevated in other tissue injuries (45). Therefore, it seems that ALT and AST concentrations alone are not sensitive enough for the diagnosis or evaluation of liver function in NAFLD especially in the early stage of disease.…”
Section: Laboratory Investigationsmentioning
confidence: 99%